Upaya Pencegahan Covid-19 Dengan Pembagian Masker Kepada Masyarakat Lingkar Tambang Batuan di Kelurahan Kalumata Kota Ternate Selatan - Hilda Alkatiri; Wawan Ak Conoras (Journal Of Khairun Community Services, 2021)
The corona virus or Covid-19 has continued to be a public concern since the beginning of 2020. This is because the virus that originated in Wuhan, China, quickly spread throughout the world, including Indonesia, especially North Maluku. With the spread of the virus, the global community is worried and afraid. The government, the private sector and the community have begun to take part in helping others who are experiencing economic downturn during the pandemic. As an effort to participate in handling the prevention of the corona virus, the Faculty of Engineering, Khairun University feels compelled to participate. Participation is carried out in the Community Service (PkM) program. The Covid-19 prevention effort by distributing masks to the community around the rock quarry in Kalumata Village, South Ternate City has been carried out by involving 5 students, non-medical masks consisting of two layers of cloth as many as 150 pieces that can be used repeatedly and can be washed were successfully distributed for free to the public within 2 days. The community feels very helped by this activity, with this activity it is hoped that it can increase public awareness in an effort to break the chain of the spread of Covid-19, namely in an orderly manner and always wear masks when outside the home, besides that the community is expected to always apply a clean and healthy lifestyle by wash your hands often and use hand sanitizer regularly, keep your distance, take vitamins, and obey the advice to stay at home